Peningkatan Mutu dan Kualitas UMKM Dengan Membangun Brand dan Brand Exposure Untuk Memperluas Segmentasi Pasar - Fauzan, Fahrul Alvin; Lestari, Erma Puji; Ardio, Karisma; Widaningrum, Ida (Society : Jurnal Pengabdian Masyarakat, 2023)
This paper aims to describe the improvement in the quality and quality of MSMEs in Manuk village, Siman sub-district, Ponorogo district by building a brand and brand exposure to MSME products in the village so that the products can be better known so that the market segmentation reached becomes wider, so that it is expected to increase sales value and product sales. This activity is one of the work programs carried out by the group in the University of Muhammadiyah Ponorogo KKN program as a form of community service where it is hoped that this activity will have an impact on the Manuk village community, especially the MSME sector in the village can develop so that community welfare also increases. The program being carried out is in the form of designing a logo and making stickers as the identity of MSME products and making attractive packaging so that the product is more attractive to consumers.